Mgtricity - a financial analysis of a microgrid for a sustainable future - Costa, Manuel Sousa Mota (2020)
Afinancial analysis for athird generation microgrid developed byMGtricityto be deployed in Kenya. We explore thenecessary assumptions for cash flowestimation and discounting, the sourcesof funds to initiate and sustain thebusinessas well as the types of risk the firm can face and how to mitigate them.Ultimately,theimplementation road mapis presented.